Promoting Social Justice for Young Children
XVI, 180 p.
Keywords: This book explores important current social justice issues that confront young children in America. A broad range of topics related to the fair treatment of young children and their families are approached with a fresh and hopeful energy. The central argument of this volume is that a fair and just society must protect the basic needs of all children so they are able to reach their full potential to learn, grow, and ultimately become productive democratic citizens. The book includes contributions from an impressive group of authors who have been consistent voices for the fair and equitable treatment of children in school and society. Each chapter examines a critical issue in child social justice with a focus on the current problem, historical importance of the issue, potential solutions, and a vision for the future. The book has been developed to reach a wide audience of professionals whose work involves children and who have grown concerned about social forces that cause child suffering and threaten the well-being or even the survival of children in the United States. Readers will come away with up to date information and a renewed commitment to being life-long advocates for children. .